A New Wind of Media Freedom: Social Media and Political Participation in Zimbabwe - Arthur Fidelis Chikerema; Tomy Ncube (Centre for Democracy, Research and Development, 2023)
Social media in Zimbabwe has brought in a modified political genealogy with a hybrid of political participation. Having had successive years of post-independence characterized by media repression and premeditated media dishes that had the same ultra-patriotism and no sense of variety, the ushering in of social media diluted the repression. From a comparative perspective of reporting based on (AIPPA) Access to Information and Protection Act, (POSA) Public and Order Security Act and (BSA) Broadcasting Services Act, social media stands uncircumcised of any of legal statutes to govern and manipulate its traction. Born out a case study approach the research was largely exploratory, seeking to investigate the impact of social media in Zimbabwe on a political note with a sample size of 3 500. The paper established that social media was strongly engrained with a sense of messianic political touch as expressed by the political freedom, digital democracy and political participation that it has brought in within the political milieu as per the respondents. Collection of data was done through conducting focus group discussions and establishing questionnaires with a response rate of 91%.